Bidding modes for renewable energy considering electricity-carbon integrated market mechanism based on multi-agent hybrid game. (15th January 2023) - Zhang, Xinyue; Guo, Xiaopeng; Zhang, Xingping
Abstract: The proposal of carbon peak and carbon neutrality goals will inevitably promote the large-scale development of renewable energy, and the market mechanism is also being pushed forward to absorb more renewable energy in China. Considering electricity-carbon integrated market mechanism, this paper constructs a hybrid game model to study the evolutionary process of renewable energy generation companies (GENCOs) in market trading by setting up three renewable energy bidding modes. Among them, the leader-follow relationship between GENCOs and the day-ahead electricity market is reflected by the Stackelberg game model, and the bidding behavior of different GENCOs is described by cooperative and non-cooperative game models. The role of different stages for the carbon emissions trading (CET) market on the electricity market is discussed based on the sensitivity analysis. The simulation results show that the bundled sales between wind, photovoltaic and thermal power GENCOs could improve the expected profits of each GENCO and reduce the total carbon emissions. As the proportion of renewable energy in the electricity market increases, the clearing prices will decrease. Meanwhile, the peak-shaving times of thermal power units will raise, and thermal power GENCOs are more willing to participate in the auxiliary service market. Besides, the complete marketization of renewable energy GENCOs will affect the recovery of the initial investment. Moreover, it can be found that lower free carbon quota, higher CET and Chinese certified emission reduction (CCER) prices can effectively guide the electricity market to be cleaner. Highlights: Propose effective bidding modes for renewable energy. Consider the impact of electricity-carbon integration mechanism on renewable energy. Determine the optimal alliance of different types GENCOs for bundling electricity. Set dynamic CET and CCER prices to better reflect market supply and demand.